Environmental Management Strategy in the Golden Era of the Poboya Village Mining Area, Mantikulore District, Palu City - Ikbal Ikbal; Gabriela Almasari Datuan; Abdullah Abdullah; Nursiah Moh. Yunus; Widyatmi Anandy (Administrative and Environtmental Law Review, 2026)
Artisanal gold mining in Poboya Village, Mantikulore District, Palu City, poses significant environmental risks due to the continued use of mercury in gold processing. Mercury contamination has degraded land and water quality and threatens public health, revealing weaknesses in both mining practices and the legal framework governing artisanal mining. This study analyzes deficiencies in artisanal mining regulations and examines the normative conflict between community and corporate mining permits within Indonesia's licensing system. It employs normative legal research using statutory, conceptual, and case approaches, drawing on mining and environmental legislation, including regulations on People's Mining Areas (WPR), supported by secondary legal sources. The findings reveal regulatory weaknesses, including unclear provisions, poor legal harmonization, and ineffective oversight. Conflicts between community and corporate mining permits create legal uncertainty and undermine environmental protection. Strengthening the legal framework through regulatory harmonization, improved WPR regulations, and more effective oversight and law enforcement is therefore essential to promote equitable, sustainable mining governance and legal certainty.